Réponses

Meilleure réponse !
2014-03-01T16:38:51+01:00
Bonjour,

R = 6x-7+9x+4 = 15x-3 = J
E = 4x²-3x+7+6x+5x²+2 = 9x²+3x+9 = E
S = 2(3x+5) + 4(2x-3) = 6x+10+8x-12 = 14x-2 = A
I = 2x(5x+3)-(8x²-2) = 10x²+6x-8x²+2 = 2x²+6x+2 = N
S = 4x²-2-(9x²-3x+4) = 4x²-2-9x²+3x-4= -5x²+3x-6 = M
T = (5x-3)(2x+4) = 10x²+20x-6x-12 = 10x²+14x-12 = O
A = 4x-2(3x-5) = 4x-6x+10 = -2x+10 = U
N = (3x-2)(-6x+4)+10x² = 10x²-18x²+12x+12x -8 = -8x²+24x-8  = L
T = 5x+(3-2x)(2+5x) +4 = 5x+6+15x-4x+10x²+4 = -10x²+16x+10 = I
S = (4-5x)(2x-8)+2x²+3 = 8x-32-10x²+40x+2x²+3= -8x²+48x-29 = N

Heureux de t'avoir aider
Jean Moulin
merci beaucoup jai essayer au moin 20 fois jai pas reussi merci merci encore